2017
DOI: 10.1016/j.anai.2016.11.008
|View full text |Cite
|
Sign up to set email alerts
|

Food allergen extracts to diagnose food-induced allergic diseases

Abstract: The manufacture of food allergen extracts requires many considerations to achieve the maximal quality of the final product. Allergen extracts for a select number of foods may be inconsistent between manufacturers or unreliable in a clinical setting, indicating a potential area for future improvement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 74 publications
0
11
0
Order By: Relevance
“…2,3 We have previously shown the increase of IgG4 to peanut seed storage proteins, and the dosedependent increase of IgG4-IgE ratios in children and adolescents receiving peanut OIT. 4,5 Further, we showed that IgE to the 2S albumins Ara h 2 and Ara h 6, which are the most important peanut allergens, 6 were the only IgE responses affected during OIT. 5 In this study, we screened IgG4 responses for a wide spectrum of allergens with the ISAC ImmunoCAP microarray in children and adolescents who underwent peanut OIT.…”
mentioning
confidence: 74%
“…2,3 We have previously shown the increase of IgG4 to peanut seed storage proteins, and the dosedependent increase of IgG4-IgE ratios in children and adolescents receiving peanut OIT. 4,5 Further, we showed that IgE to the 2S albumins Ara h 2 and Ara h 6, which are the most important peanut allergens, 6 were the only IgE responses affected during OIT. 5 In this study, we screened IgG4 responses for a wide spectrum of allergens with the ISAC ImmunoCAP microarray in children and adolescents who underwent peanut OIT.…”
mentioning
confidence: 74%
“…Purified antigens in diagnostic allergy tests are not necessarily more effective than complex protein solutions [21]. Albeit all efforts there are still inconsistencies between manufacturers of food allergens which may turn the tests unreliable in the clinical setting [22].…”
Section: Discussionmentioning
confidence: 99%
“…37 Depending upon the specific food item, heating and/or cooking may increase, decrease or have no effect on its allergenicity. [37][38][39] For example, in humans, heat-induced Maillard reactions between carbohydrates and amino acids have been demonstrated to create new IgE-binding epitopes in peanuts, whereas the same process decreased the allergenicity of tropomyosin derived from mud crabs. 40,41 Re-evaluation using cooked ingredients (preferably under conditions similar to those involved in processing into kibble) may be required.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, commercially available food allergen extracts are typically prepared from raw source materials, whereas most dogs eat these proteins in their processed (i.e. cooked) form . Depending upon the specific food item, heating and/or cooking may increase, decrease or have no effect on its allergenicity .…”
Section: Discussionmentioning
confidence: 99%